As dificuldades encontradas pelos profissionais de saúde na implantação e execução dos Testes Diagnósticos Rápidos na atenção primária a saúde: uma revisão integrativa - Guará, Andrea Chaves Malaman (Universidade Federal de São Carlos, 2022)
The use of rapid diagnostic testing (RDT) in primary health care (PHC) is one of the strategies of the Brazil's Ministry of Health to make it easier for people to access to timely diagnosis of some diseases of interest to individual and collective health, such as infections by human immunodeficiency virus (HIV), hepatitis B and C virus, bacillus that causes syphilis, SARS- Cov- 2 and others. RDT are immunochromatographic assays that allow quickly detection of the presence of antigen or antibody in the specimen tested. Its have the advantage of being easy to store and transport for collect in the field, without need of sophisticated techniques or reagents of difficult preservation. Thus, is not necessary complex laboratory structure for its execution, reading and interpretation. Its realization delay up to 30 minutes, considering all steps, what collaborates to reduce the overhead of central laboratories. It is hypothesized that PHC faces difficulties in incorporating this technology into the routine of services due to various contingencies. Objective: To describe the difficulties of PHC professionals in relation to the decentralization and implementation of RDT. Methodology: This is an integrative literature review carried out from March 2021 to July 2022. The data search was performed online on the SCIELO, PubMed, Google Scholar and virtual health library (VHL) data platforms. Because “quick test” is not a descriptor, we choset o search with words that, when associated, could refer to “rapid test”. (HIV; Human Viral Hepatitis; Syphilis serology; acquired immunodeficiency syndrome (AIDS) serology; serological tests, sexually transmitted diseases). This dissertation is the conclusion work of a professional master course, through which it was possible to elaborate a training proposal for the application of rapid tests in PHC. Results: 2,200 publications were found: 70 were duplicates and 579 were excluded; 21 were used in this integrative review. Conclusion: The process of decentralization of rapid testing in PHC is in progress and occurs unevenly in units across the country. Thus, among the difficulties encountered by health professionals, the lack of adequate environment and materials, deficiency in team training, insecurity of professionals in carrying out rapid tests in the delivery of results and work overload. Health professionals who work in PHC, in the process of decentralization and implementation of rapid tests, have similar opinions regarding this process, they know the importance of testing in the direct improvement of the population's health, they believe in a new model of health care, however, they report the difficulties mentioned above.
The difficulties found by health professionals in the implementation and execution of Rapid Diagnostics Tests in primary health care: an integrative review.
Keywords: Atenção primária; Testagem; Doenças sexualmente transmissíveis; Descentralização; Testing; Sexually transmitted diseases; Primary care; Decentralization; CIENCIAS BIOLOGICAS